Surgical Management of Zygomatico-Maxillary Complex Fractures in Enam Medical College Hospital, Savar: A Retrospective Study of 70 Cases (Journal of Enam Medical College, 2024)
Background:  The incidence of maxillofacial injuries is on the rise due to motor vehicle accidents and increased incidence of violence in recent times. Zygomatic bone is closely associated with the maxilla, frontal, and temporal bones which are usually involved when a zygomatic bone fracture occurs. Objective:  The aim of this retrospective study was to determine clinical presentations, the pattern of fractures, their management (open reduction and internal fixation), outcome and complications in a tertiary level hospital. Materials and Methods: This retrospective analysis of all operative cases (open reduction and internal fixation) of zygomatic complex fractures was carried out in the Maxillofacial Surgery Department, Enam Medical College & Hospital, Savar, Dhaka during  the period of January 2018 to December 2021. Data were obtained from clinical notes and surgical records of the patients using standardized data collection form specifically designed to examine the variables and features of zygomatic complex fractures. Results: Seventy patients were allocated to surgical intervention. Two-point internal fixation was done in more than half (57.1%) of the cases. Six (8.6%) patients developed postoperative complications like paraesthesia, ectropion, scar, facial asymmetry. Twenty-five (35.7%) patients were found having limited mouth opening preoperatively and postoperative improvement occurred in 24 patients. All the patients had facial asymmetry preoperatively and postoperative improvement occurred in most cases. Only one patient had facial asymmetry in one year follow up. Conclusion: There is no consensus on standard treatment of zygomatic complex fractures, as made evident by the survey. Significant variability in fracture type warrants an individualized approach to management. A thorough review on zygomatic complex fracture management is provided.J Enam Med Col 2022; 12(2): 102−108